Effect of Vacancy on Physical Properties of Cmcm Si24 - Jia, M.; Fan, Q.; Hao, B.; Zhao, Y.; Song, Y.; Yun, S. (Acta Physica Polonica A, 2024)
Researchers recently synthesized a new orthorhombic allotrope of silicon, namely Cmcm Si24. This work studied the effect of one vacancy for Cmcm Si24 on structural, electronic, and mechanical anisotropy properties by the first principle calculation. The lattice parameters of Cmcm Si24:V are the same as Cmcm Si24, but the density of Cmcm Si24:V is larger than that of Cmcm Si24. Moreover, the values of elastic moduli for Cmcm Si24:V are smaller than for Cmcm Si24. The Cmcm Si24:V has mechanical stability and anisotropy and has lower formation energy than diamond-Si. The analysis of the band structures shows that Cmcm Si24 is an indirect band gap material, and the value of the band gap is 1.08 eV. In particular, electronic band structures of Cmcm Si24:V exhibit metallic characteristics. Furthermore, the electron localization function indicated strong covalent silicon–silicon bonds in Cmcm Si24 and Cmcm Si24:V. In addition, the effective mass of electrons and holes of Cmcm Si24 is smaller than that of diamond-Si along the a direction, and larger than that along the b and c directions. Finally, the X-ray diffraction patterns for Cmcm Si24 and Cmcm Si24:V are very close after 13.84°C.